2014
DOI: 10.1002/2013ja019297
|View full text |Cite
|
Sign up to set email alerts
|

Energy coupling during the August 2011 magnetic storm

Abstract: We present results from an analysis of high-latitude ionosphere-thermosphere (IT) coupling to the solar wind during a moderate magnetic storm which occurred on 5-6 August 2011. During the storm, a multipoint set of observations of the ionosphere and thermosphere was available. We make use of ionospheric measurements of electromagnetic and particle energy made by the Defense Meteorological Satellite Program and neutral densities measured by the Gravity Recovery and Climate Experiment satellite to infer (1) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 49 publications
4
67
0
2
Order By: Relevance
“…In a comparison of particle precipitation with solar radiation and Joule heat, Knipp et al (2004) arrived at a ratio of particle to Joule heat of approximately 1:10 for large storms. In our study of the August 2011 storm, we estimated the precipitation power as well as the observed Poynting flux and reached similar ratios (Huang et al 2014a). It is clear that Poynting flux is the dominant form of energy input to the IT system.…”
Section: Ionospheric Response To Solar Wind Forcing -Observationssupporting
confidence: 58%
See 4 more Smart Citations
“…In a comparison of particle precipitation with solar radiation and Joule heat, Knipp et al (2004) arrived at a ratio of particle to Joule heat of approximately 1:10 for large storms. In our study of the August 2011 storm, we estimated the precipitation power as well as the observed Poynting flux and reached similar ratios (Huang et al 2014a). It is clear that Poynting flux is the dominant form of energy input to the IT system.…”
Section: Ionospheric Response To Solar Wind Forcing -Observationssupporting
confidence: 58%
“…Figure 1 shows the solar wind conditions for the three storms presented here. The first storm onset occurred on August 5, 2011 and was the subject of our earlier paper on the energy budget (Huang et al 2014a). We take the end of the main phase (MP) to be at the minimum in Sym H at 0327 UT, or Day of Year (DOY) 218.14.…”
Section: Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations